Blue light emitting diodes irradiation causes cell death in colorectal cancer by inducing ROS production and DNA damage. (October 2018) - Yan, Gege; Zhang, Lai; Feng, Chao; Gong, Rui; Idiiatullina, Elina; Huang, Qihe; He, Mingyu; Guo, Shuyuan; Yang, Fan; Li, Yuan; Ding, Fengzhi; Ma, Wenya; et al.
Abstract: The light emitting diodes (LEDs) irradiation has been demonstrated to be potential therapeutic strategies for several diseases. However, the blue LED effects remain largely unknown in colorectal cancer (CRC), which is a major cause of morbidity and mortality throughout the world. In this study, we determined the effects of blue LED irradiation, the maximal light emission at 470 nm in wavelength, in human CRC cell lines SW620 and HT29. The cells were irradiated with blue LED light for 0 J/cm 2, 72 J/cm 2, 144 J/cm 2, 216 J/cm 2 and 288 J/cm 2 respectively. We found that irradiation with blue LED light induced a marked decrease of live cells and an increase of dead cells. Additionally, lower cell proliferation and a remarkably increase of cell apoptosis were observed in blue LED-irradiated cells as compared with non-irradiated control group. The cell migration was significantly inhibited by blue LED irradiation 24, 48 and 72 h later compared with non-treated group. Blue LED-treated CRC cells further displayed a remarkably inhibition of EMT process in CRC cells. Finally, we found the accumulation of ROS production and DNA damage were induced by blue LED irradiation. These results indicated that blue LED irradiation inhibits CRC cell proliferation, migration and EMT process as well as induces cell apoptosis, which may result from increased ROS accumulation and induction of DNA damage.